UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KECERDASAN EMOSIONAL SISWA - Abdul Fatahillah (UNISAN JURNAL, 2024)
The aim of this research is to determine the efforts of Islamic religious education teachers in increasing emotional intelligence at the educational institution. This type of research is qualitative descriptive research, namely research procedures that produce descriptive data. In data collection techniques in this research, various techniques were used, namely interviews, observation and documentation. The data analysis procedure used in this research is qualitative analysis. Based on research, it can be concluded that the efforts of Islamic religious education teachers are carried out in a planned, systematic and sustainable manner. In the implementation of the learning carried out by the teacher, the principal’s attitude apparently did not interfere with the recording process in class, in fact the principal at the end of the lesson motivated the students to continue studying diligently. It is known that teachers have good performance in the learning process, this can be seen from the process of preparing learning plans which are prepared in accordance with the criteria set out in the teacher performance standards, at the learning implementation stage the teacher is able to master the class, master the material well, so the teacher is able to vary the methods teaching and using learning media and providing opportunities for students to interact with questions and answers. The problem in the efforts of Islamic religious education teachers to improve teacher performance in schools is the low motivation of teachers to carry out supervision.